Multi-environment Assessment of Combining Ability, Heterosis of Bt Introgressed Lines and Hybrids of Upland Cotton (Gossypium hirsutum L.) - Samak, Ashwini N. R.; S., Rajeswari; R, Ravikesavan .; Lokanadhan, Subbalakshmi; Ganapathy, N.; Kini, A. V. (International Journal of Bio-resource and Stress Management, 2022)
A study was conducted at Dharwad, Raichur and Aurangabad in India during the rainy season of 2018 to investigate the environmental impact on combining ability and heterosis estimates in cotton. Combining ability analysis across locations showed significant effects on the performance of genotypes, GCA, SCA, genotype×environment, GCA×environment and SCA×environment interactions for most of the characters. Combining ability variance revealed the predominance of non-additive gene actions for characters under study. The parents and crosses varied with locations for combining ability and better parent heterosis estimates. Out of 22 parents, ten parents recorded high overall gca and among them, two BGII, six BGI and two non-Bt parents were under study. Similarly, 55 hybrids were exhibited high overall sca and better parent heterosis from the study and most of the crosses were derived from lines crossed with high overall gca (H) with low overall gca (L) or vice versa. This study indicated the requirement of parents with contrasting gca effects to realize a higher frequency of heterotic hybrids. The predominance of H×L type of crosses indicated the presence of non-additive gene action suggesting exploitation of good heterotic hybrids from the study. The frequency of hybrids with high overall sca and heterobeltiosis was more in BG II hemizygous hybrids compared to BG II homozygous condition with H×L type. Similar were the results with BGI hemizygous hybrids.